Answers

2014-09-28T19:54:25+08:00
Let 'x' be the number 
    'y' be the other number 
x + y = 25  -----equation 1
y = x + 9   ------equation 2

substitute equation 2 to equation 1
x + x + 9 = 25
combine the terms
x + x = 25 - 9
2x = 16
x = 8
substitute the value for x in equation 2
y = x + 9
y = 8 + 9
y = 17
1 5 1
2014-09-28T20:15:01+08:00
Let 'x' be the number 
    'y' be the other number 
x + y = 25  -----equation 1
y = x + 9   ------equation 2

substitute equation 2 to equation 1
x + x + 9 = 25
combine the terms
x + x = 25 - 9
2x = 16
x = 8
substitute the value for x in equation 2
y = x + 9
y = 8 + 9
y = 17
0